The genome sequence of the Vapourer moth, Orgyia antiqua (Linnaeus, 1758) [version 2; peer review: 2 approved] - Douglas Boyes; Jamie C. Weir (Wellcome Open Research, 2024)
We present a genome assembly from an individual male Orgyia antiqua specimen (the Vapourer moth; Arthropoda; Insecta; Lepidoptera; Erebidae). The genome sequence is 480.1 megabases in span. Most of the assembly is scaffolded into 14 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.4 kilobases in length. Gene annotation of this assembly on Ensembl identified 12,475 protein coding genes.